The Effect of Deep Breathing Technique on Children’s Concentration - Azmi Maulidah; Very Julianto (Universitas Ahmad Dahlan, 2022)
One of the developmental tasks a child should complete is to concentrate. However, some children failed to concentrate, causing difficulty in processing the stimulus thoroughly. This study aimed to determine the effectiveness of deep breathing techniques in improving children’s concentration. Applying the pretest-posttest control group quasi-experimental method, this study involved sixteen students who were assigned into experimental (n=9) and control (n=7) groups. Participants were selected using a purposive sampling technique. The data were collected using digit span and analyzed using Mann-Whitney U. The study result showed that the deep breathing technique was effective in improving children’s concentration. Thus, school counselors are recommended to optimize deep breathing techniques to improve their concentration.